Quality of Life in Patients with Knee Osteoarthritis: A Cross-Sectional Study in Baaquba City: Kualitas Hidup pada Pasien Osteoartritis Lutut: Sebuah Studi Cross-Sectional di Kota Baaquba - Najim , Akram Abd Alsalam; Faleh , Ali Husain; Noaman , Aqeel Abbas (Academia Open, 2024)
Background: Knee osteoarthritis (KOA) is a common degenerative joint disease that significantly impacts the quality of life (QoL) of elderly individuals, often leading to severe disability. Specific Background: KOA, a prevalent condition primarily affecting middle-aged women, is exacerbated by risk factors like obesity, genetics, and reduced physical activity. Knowledge Gap: Despite existing studies on KOA, there is limited research on its impact on QoL in the Iraqi context, particularly in Baqubah City. Aims: The study evaluated the quality of life (QoL) of KOA patients in Baqubah, Iraq, considering physical, psychological, social, and functional aspects, and identifying influencing factors. Results: Data were collected from 374 patients at Baqubah Teaching Hospital, using a structured and validated HRQOL questionnaire. The study revealed that KOA patients experienced a significantly reduced QoL, especially in the physical and functional domains. Females and those with a longer illness duration reported worse outcomes. Obesity and overweight were found to be common among patients, further exacerbating the disease. Novelty: This study evaluates KOA's impact on QoL in Baqubah, revealing high prevalence and significant negative effects on daily activities. Implications: The study highlights the need for targeted interventions to enhance the quality of life for KOA patients in Baqubah, focusing on weight management, physiotherapy, and improved public health strategies. Highlights: KOA severely impairs physical and functional quality of life in patients. Obesity and inactivity are key modifiable risk factors for KOA. Women and long-term sufferers face greater QoL challenges. Keywords: Knee Osteoarthritis, Quality of Life, Risk Factors, Obesity, Baqubah